Effectiveness of a group-based self-management program for people with chronic fatigue syndrome: a randomized controlled trial. (January 2017) - Pinxsterhuis, Irma; Sandvik, Leiv; Strand, Elin Bolle; Bautz-Holter, Erik; Sveen, Unni
Objective: To evaluate the effectiveness of a group-based self-management program for people with chronic fatigue syndrome. Design: A randomized controlled trial. Setting: Four mid-sized towns in southern Norway and two suburbs of Oslo. Subjects: A total of 137 adults with chronic fatigue syndrome. Intervention: A self-management program including eight biweekly meetings of 2.5 hours duration. The control group received usual care. Main measures: Primary outcome measure: Medical Outcomes Study-Short Form-36 physical functioning subscale. Secondary outcome measures: Fatigue severity scale, self-efficacy scale, physical and mental component summary of the Short Form-36, and the illness cognition questionnaire (acceptance subscale). Assessments were performed at baseline, and at six-month and one-year follow-ups. Results: At the six-month follow-up, a significant difference between the two groups was found concerning fatigue severity ( p  = 0.039) in favor of the control group, and concerning self-efficacy in favor of the intervention group ( p  = 0.039). These significant differences were not sustained at the one-year follow-up. No significant differences were found between the groups concerning physical functioning, acceptance, and health status at any of the measure points. The drop-out rate was 13.9% and the median number of sessions attended was seven (out of eight). Conclusions: The evaluated self-management program did not have any sustained effect, as compared with receiving usual care.